HOMOSEKSUALITAS DALAM PANDANGAN PEMIKIR BARAT DAN FUKAHA - Salma Salma (State Islamic University North Sumatra, 2008)
Abstract: Homosexuality in the Perspective of Western Thinkers and Islamic Jurisprudents. It is widely accepted that homosexuality is a damaging and immoral way of life. This presupposition seems to become as a uniting factor between the thoughts of Western scholars and Islamic jurisprudents on the legal position of homosexuality. The author argues that although Islam respect freedom in all aspects of life which belongs to every single individual, however, freedom is always recompensed with contractual responsibility to control its proper use and misuse. Accordingly, in the reality of Western world not all of the society is in agreement with substantial use of freedom occurs around them. Freedom demanded by homosexuality and social reality has led to serious concern amongstthe society about their future generation. In such a condition their human nature points to the necessity for religious and spiritual life. The author argues that they trust religion to be capable of anticipating themselves as well as their family from negative effect of homosexuality. This essay analyzes the root of homosexuality in the view of both Western scholars and Islamic jurisprudents, and relates their implication to the importance of religion. Kata Kunci: kebebasan, homosexualitas, pemikir Barat, fukaha